Effects of metformin on the adrenal cortex of androgenized rats. (3rd August 2015) - Macedo, Lilian Alves; Carbonel, Adriana Aparecida Ferraz; Simões, Ricardo Santos; Fuchs, Luiz Fernando Portugal; do Amaral, Vinicius Cestari; Simoncini, Tommaso; Simões, Manuel Jesus Santos; Baracat, Edmund Chada; Maria Soares, José
Abstract: Objective : To evaluate the sex steroid profile and histomorphometry of the adrenal cortical zones of androgenized rats ( wistar ) with polycystic ovary syndrome treated with metformin. Study design : Thirty animals were divided into three groups: GC (regular estrous cycle), GPE (permanent estrus), and GPEM (permanent estrus + metformin 28 mg/kg for 50 days). At the end of this period, blood was collected for hormone measurement. The width of the adrenal cortical zones and the nuclear volumes were analyzed by histomorphometry. The ANOVA test was used in the statistical analysis. Results : The adrenal glands of the androgenized animals were larger and more intensely vascularized than those of the other groups. The concentration of androstenedione in GPE was higher than that in the other groups (0.4 ± 0.1*>= 0.2 ± 0.1 = 0.2 ± 01, * p  < 0.05). The width of the zona glomerulosa and of the zona reticularis and their nuclear volumes were greater in GPE compared to those of the other groups (GPE* > GPEM = GC, * p  < 0.05). Conclusion : Metformin treatment may decrease the serum levels of androstenedione as well as the width and the nuclear volumes of the zona glomerulosa and of the zona reticularis in androgenized animals. Chinese abstract: 目的： 评价二甲双胍治疗后的多囊卵巢综合征的雄激素化大鼠（wistar）肾上腺皮质区性类固醇简况及组织形态学。 实验设计： 三十只大鼠被分为三组：GC(规律发情周期组)，GPE（持续发情组）和GPEM（持续发情+二甲双胍28 mg/kg治疗50天）。这段时期结束后，采集血样进行激素测定。肾上腺皮质区的宽度和核体积采用组织形态测定技术进行分析。采用ANOVA分析进行数据分析。 结果： 雄激素化大鼠相比其他组，肾上腺更大且血管化更强烈。GPE组中的雄烯二酮水平高于其他组 (0.4 ± 0.1*＞=0.2 ± 0.1=0.2 ± 01, *p<0.05)。PE组肾上腺球状带宽度和网状带宽度及胞核体积相比其他组更大(GPE*＞GPEM=GC, *p<0.05)。 结论 ： 二甲双胍治疗可降低雄激素化动物的雄烯二酮血清水平以及球状带和网状带的宽度和胞核体积。